Efficient synthesis of cucurbiturils and their derivatives using mechanochemical high-speed ball milling (HSBM). (June 2021) - Xu, Wenhao; Li, Chengyu
Under solid-phase conditions, mechanical ball milling can be used to selectively prepare cucurbit[6]uril (CB[6]) and its derivatives without the use of catalysts and solvents. Using response surface method to determine the optimal conditions for the synthesis of CB[6]. The yield of CB[6] and its derivatives is 75–95%, with a high selectivity of more than 95%. In the synthesis of CB[6] using this method, the amount of acid required is significantly less, no organic solvent is needed, and the preparation of the fully aryl-substituted CB[6] is possible, which is otherwise difficult to be synthesized directly using traditional methods. Mechanical ball milling, thus, is of great significance in the synthesis and research of new cucurbituril supramolecules. Process scale-up experiments show that the yield and selectivity of the various types of cucurbiturils is higher than 95%, because of which they find good industrial applications.